Polysubstance use and association with opioid use disorder treatment in the US Veterans Health Administration. (7th July 2020) - Lin, Lewei A.; Bohnert, Amy S. B.; Blow, Frederic C.; Gordon, Adam J.; Ignacio, Rosalinda V.; Kim, H. Myra; Ilgen, Mark A.
Abstract: Aims: To understand the role of comorbid substance use disorders (SUDs), or polysubstance use, in the treatment of opioid use disorder (OUD), this study compared patients with OUD only to those with additional SUDs and examined association with OUD treatment receipt. Design, setting and participants: Retrospective national cohort study of Veterans diagnosed with OUD ( n = 65 741) receiving care from the US Veterans Health Administration (VHA) in fiscal year (FY) 2017. Measurements: Patient characteristics were compared among those diagnosed with OUD only versus those with one other SUD (OUD + 1 SUD) and with multiple SUDs (OUD + ≥ 2 SUDs). The study examined the relationship between comorbid SUDs and receipt of buprenorphine, methadone and SUD outpatient treatment during 1‐year follow‐up, adjusting for patient demographic characteristics and clinical conditions. Findings: Among the 65 741 Veterans with OUD in FY 2017, 41.2% had OUD only, 22.9% had OUD + 1 SUD and 35.9% had OUD + ≥ 2 SUDs. Common comorbid SUDs included alcohol use disorder (41.3%), cocaine/stimulant use disorder (30.0%) and cannabis use disorder (22.4%). Adjusting for patient characteristics, patients with OUD + 1 SUD [adjusted odds ratio (aOR) = 0.87, 95% confidence interval (CI) = 0.82–0.93] and patients with OUD +≥ 2 SUDs (aOR = 0.65, 95% CI = 0.61–0.69) had lower odds of receiving buprenorphine compared with OUD only patients. There were also lower odds of receiving methadone for patients with OUD + 1 SUD (aOR = 0.91, 95% CI = 0.86–0.97)and for those with OUD + ≥2 SUDs (aOR = 0.79, 95% CI = 0.74–0.84). Patients with OUD + 1 SUD (aOR = 1.85, 95% CI = 1.77–1.93) and patients with OUD + ≥2 SUDs (aOR = 3.25, 95% CI = 3.103.41) were much more likely to have a SUD clinic visit. Conclusions: The majority of Veterans in the US Veterans Health Administration diagnosed with opioid use disorder appeared to have at least one comorbid substance use disorder and many have multiple substance use disorders. Despite the higher likelihood of a substance use disorder clinic visit, having a non‐opioid substance use disorder is associated with lower likelihood of buprenorphine treatment, suggesting the importance of addressing polysubstance use within efforts to expand treatment for opioid use disorder.